South Indian Isolates of the Fusarium solani Species Complex From Clinical and Environmental Samples: Identification, Antifungal Susceptibilities, and Virulence - Homa, Mónika; Galgóczy, László; Manikandan, Palanisamy; Narendran, Venkatapathy; Sinka, Rita; Csernetics, Árpád; Vágvölgyi, Csaba; Kredics, László; Papp, Tamás (Frontiers in Microbiology, 2018)
Members of the Fusarium solani species complex (FSSC) are the most frequently isolated fusaria from soil. Moreover, this complex solely affects more than 100 plant genera, and is also one of the major opportunistic human pathogenic filamentous fungi, being responsible for approximately two-third of fusariosis cases. Mycotic keratitis due to Fusarium species is among the leading causes of visual impairment and blindness in South India, but its management is still challenging due to the poor susceptibility of the isolates to conventional antifungal drugs. Aims of the present study were to isolate South Indian clinical and environmental FSSC strains and identify them to species level, to determine the actual trends in their susceptibilities to antifungal therapeutic drugs and to compare the virulence of clinical and environmental FSSC members. Based on the partial sequences of the translation elongation factor 1α gene, the majority of the isolates – both from keratomycosis and environment – were confirmed as F. falciforme, followed by F. keratoplasticum and F. solani sensu stricto. In vitro antifungal susceptibilities to commonly used azole, allylamine and polyene antifungals were determined by the CLSI M38-A2 broth microdilution method. The first generation triazoles, fluconazole and itraconazole proved to be ineffective against all isolates tested. This phenomenon has already been described before, as fusaria are intrinsically resistant to them. However, our results indicated that despite the intensive agricultural use of azole compounds, fusaria have not developed resistance against the imidazole class of antifungals. In order to compare the virulence of different FSSC species from clinical and environmental sources, a Drosophila melanogaster model was used. MyD88 mutant flies having impaired immune responses were highly susceptible to all the examined fusaria. In wild-type flies, one F. falciforme and two F. keratoplasticum strains also reduced the survival significantly. Pathogenicity seemed to be independent from the origin of the isolates.